EFFECT OF FIXED ASSETS MANAGEMENT AND INVESTMENT DECISIONS ON PERFORMANCE OF FRUIT FARMING IN KENYA: A CASE OF MACHAKOS COUNTY - Nyamai, Luciana Muthoki (European Journal of Business and Strategic Management, 2018)
Purpose: The purpose of this study was to establish the effect of fixed assets management and investment decisions on performance of fruit farming. Methodology: Descriptive research and correlation research design were used in this study. The target population in this study was fruit farmers in Mwala Sub County in Machakos County who were 2702. Quota sampling technique was used and the sample size was 348. Primary data was collected using a questionnaire. Quantitative data was analyzed by use of descriptive and inferential statistics (correlation). Qualitative data collected was analyzed using content analysis technique. The findings of this study were presented in tables, charts and graphs. Results: The study established that fixed assets management has a positive and significant correlation with performance of fruit farming. The results also showed that investment decisions have a positive and significant correlation with performance of fruit farming. Unique Contribution to Theory, Policy and Practice: Based on the study findings, the researcher recommended that so as to boost their yield, farmers need to use practices that can speed up the productivity such as using fertilizer and sprays. The study was also recommended that the extension officers need to provide the necessary support to them regarding farming.